Mesoscopic and Microscopic Magmatic Structures in the Quxu Batholith of the Gangdese Belt, Southern Tibet: Implications for Multiple Hybridization Processes - Xuxuan Ma (Frontiers Media S.A., 2021)
The Quxu batholith of the Gangdese magmatic belt, southern Tibet, comprises predominantly Early Eocene calc-alkaline granitoids that feature a variety of types of magmatic microgranular enclaves and dikes. Previous studies have demonstrated that magma mixing played a crucial role in the formation of the Quxu batholith. However, the specific processes responsible for this mixing/hybridization have not been identified. The magmatic microgranular enclaves and dikes preserve a record of this magma mixing, and are therefore an excellent source of information about the processes involved. In this study, mesoscopic and microscopic magmatic structures have been investigated, in combination with analyses of mineral textures and chemical compositions. Texturally, most of the enclaves are microporphyritic, with large crystals such as clinopyroxene, hornblende, and plagioclase in a groundmass of hornblende, plagioclase, and biotite. Two types of enclave swarms can be distinguished: polygenic and monogenic swarms. Composite dikes are observed, and represent an intermediate stage between undisturbed mafic dike and dike-like monogenic enclave swarms. Our results reveal three distinct stages of magma mixing in the Quxu batholith, occurring at depth, during ascent and emplacement, and after emplacement, respectively. At depth, thorough and/or partial mixing occurred between mantle-derived mafic and crust-derived felsic magmas to produce hybrid magma. The mafic magma was generated from the primitive mantle, whereas the felsic end-member was produced by partial melting of the preexisting juvenile crust. Many types of enclaves and host granitoids are thus cogenetic, because all are hybrid products produced by the mixing of the two contrasting magmas in different proportions. In the second stage, segregation and differentiation of the hybrid magma led to the formation of the host granitoids as well as various types of magmatic microgranular enclaves. At this stage, mingling and/or local mixing happened during ascent and emplacement. In the final stage, mafic or hybrid magma was injected into early fractures in the crystallizing and cooling pluton to form dikes. Some dikes remained undisturbed, whereas others experienced local mingling and mixing to form composite dikes and eventually disturbed dike-like monogenic enclave swarms. In summary, our study demonstrates the coupling between magmatic texture and composition in an open-system batholith and highlights the potential of magmatic structures for understanding the magma mixing process.